Investigating Causes that Affect Students’ Motivation Toward Studies - Abdul Basheer, Abdul Naeem; Haqhparast, Munir Ahmad; Charkhi, Khwaja Mohammad (Randwick International of Education and Linguistics Science Journal, 2025)
Although motivation is the most important factor influencing students’ studies progress, some students remains disinterested to their school subjects and becomes behind in their studies. The present study investigates the factors that affect Afghan students disinterest towards studies in the public high schools of the central district of Wardak province. The statistical population of the study consists of all teachers in the public high schools of the central district of Wardak, total 200 teachers. The data is collected from 100 teachers using a researcher-designed questionnaire containing 92 questions. This research employs a quantitative methodology to examine two key factors (personal and environmental) influencing student disinterest. The data were collected and analyzed using SPSS software. The findings of the study indicate that the factors affecting students’ interest toward studies include their basic needs, such as physiological, belonging, security, respect, and self-actualization, as well as environmental factors like facilities, rewards, punishment, and teachers’ professional competency. Among these, teacher professional competency and rewards have the greatest impact on student interest, while factors such as self-actualization, respect, security, punishment, belonging, physiological needs, and facilities also play significant roles. In order to foster students' interest in their studies, it is not only essential to fulfill their primary needs, but also to create an appropriate learning environment for them. Additionally, teachers who possess professional competency, mastery of subject knowledge, and strong ethical conduct are crucial for students becoming interested toward their learning.